Norme za vrednotenje telesnih lastnosti in gibalnih sposobnosti mladih odbojkarjev - Zadražnik, Marko (Šport (Ljubljana), 2022)
The study aimed to establish the norms for evaluation of results of some physical characteristics and motor abilities based on several years’ measurements of promising volleyball players, aged 14 and 15 years. The study sample included 356 male volleyball players who competed in the Regional Team Tournaments in the 2015–2019 period. The sample of variables consisted of 3 measurement procedures for evaluation of physical characteristics and 10 for evaluation of motor abilities. The norms were expressed as percentiles. We also investigated whether there were any statistically significant differences in terms of selected physical characteristics and motor abilities between the players from regional teams who were later selected for the national teams (U17, U18 and U20) and those who were not. There were no statistically significant differences between the two groups of 14-year-old boys, whereas statistically significant differences were seen with 15-year-old boys in terms of the results of two measurement procedures: landing height with a running start in attack (MMENVOZ) and landing height in block (MSMENDVB). The Slovenian national team members achieved better (higher) results in most measurement procedures. Based on these findings, it can be concluded that the use of this measurement battery is a suitable tool for first evaluation of promise and that it is also helpful when selecting volleyball players for Slovenian youth national teams.
Keywords: dečki; gibalne sposobnosti; odbojka; šport; športne reprezentance; telesne sposobnosti